Hunting for "Dirtbags" : Why Cops Over-Police the Poor and Racial Minorities - Way, Lori Beth (Book collections on Project MUSE., 2013)
An inside look at police discretionary actions and their consequences for poor communities. This ethnographic study, which includes participant observation research and in-depth interviews with police officers in a major California city and a large East Coast city, explores how police officers use their discretionary time on the job - and the consequences. Providing insights into police discretion, the authors show that America's "tough on crime" approach to justice has too often proved to be a smoke screen for controlling people deemed undesirable, rather than a genuinely effective strategy for reducing crime.